2017
DOI: 10.1097/pts.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Shared Mental Models and Mutual Trust on General Medical Units: Implications for Collaboration, Teamwork, and Patient Safety

Abstract: Although many efforts have been directed at improving nurse-physician collaboration, more work is needed. To that end, we propose increasing knowledge about their respective roles, providing opportunities for nurse and physician collaboration through rounding or committee work and enhancing the preparedness and professionalism of interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 32 publications
2
39
0
1
Order By: Relevance
“…Nursing work and nursing teams have been relatively under studied in human factors and ergonomics compared to other healthcare teams, but clearly nursing work is central to patient care and worthy of further investigation. The study did not investigate the functioning of interprofessional teams, which are important in delivering high quality care for older people, and which might pose greater challenges to effective team-working than we found in the nursing teams (Ginsburg and Bain 2017;McComb et al, 2017).…”
Section: Implications Of the Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Nursing work and nursing teams have been relatively under studied in human factors and ergonomics compared to other healthcare teams, but clearly nursing work is central to patient care and worthy of further investigation. The study did not investigate the functioning of interprofessional teams, which are important in delivering high quality care for older people, and which might pose greater challenges to effective team-working than we found in the nursing teams (Ginsburg and Bain 2017;McComb et al, 2017).…”
Section: Implications Of the Resultsmentioning
confidence: 89%
“…Teamwork in healthcare is the co-ordination of the work of several people towards the common goal of providing safe, high quality patient care (Salas et al, 2008a;Leonard et al, 2004). Constantly changing membership and spatially distributed team members (McComb et al, 2017) make teamwork in healthcare particularly challenging. The importance of teamwork is confirmed by studies showing that poor communication and ineffective teamworking are often implicated in adverse events (e.g., Nagpal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Figure , we demonstrate what a set of shared mental models about team member roles might look like for a cancer survivor. Shared mental models have been utilised in healthcare research in evaluating team behaviours on medical floors, integrated care, simulated trauma teams and simulated anaesthesia scenarios (Burtscher, Kolbe, Wacker, & Manser, ; Evans & Baker, ; McComb, Lemaster, Henneman, & Hinchey, ; Westli, Johnsen, Eid, Rasten, & Brattebo, ). Thus, shared mental models will be used as the framework for this study to emphasise the convergent and divergent views of individuals involved in cancer survivorship care.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…7 Studies have shown that the nurse–physician collaboration is of high importance and is a critical component in the delivery of safe patient care. 8 10 The implementation of quality management systems has also been shown to be conducive to teamwork and a safety climate. 9 There is evidence that improved safety climate and teamwork are associated with decreases in both patient harm and hospital mortality.…”
Section: Introductionmentioning
confidence: 99%